Audit of Co-Management and Critical Care Outreach for High Risk Postoperative Patients (The POST Audit): The Austin Health Post-Operative Surveillance Team Investigators (Post)††. Issue 6 (November 2013) - Story, D. A.; Shelton, A.; Jones, D.; Heland, M.; Bellomo, R.
Co-management and critical care outreach for high risk surgical patients have been proposed to decrease postoperative complications and mortality. We proposed that a clinical project with postoperative co-management and critical care outreach, the Post Operative Surveillance Team: (POST), would be associated with decreased hospital length of stay. We conducted a retrospective before (control group) and after (POST group) audit of this hospital program. POST was staffed for four months in 2010 by two intensive care nurses and two senior registrars who conducted daily ward rounds for the first five postoperative days on high risk patients undergoing inpatient general or urological surgery. The primary endpoint was length of hospital stay and secondary endpoints were Medical Emergency Team (MET) calls, cardiac arrests and in-hospital mortality. There were 194 patients in the POST group and 1, 185 in the control group. The length of stay in the POST group, median nine days (Inter-quartile range [IQR]: 5 to 17 days), was longer than the control group, median seven days (IQR: 4 to 13 days): difference two days longer (95.0% confidence interval [95.0% CI]: 1 to 3 days longer, P <0.001). There were no important differences in the proportion of patients having MET calls (16.0% POST versus. 13% control ( P =0.25)) or mortality (2.1% POST versus 2.8% Control ( P =0.82)). Our audit found that the POST service was not associated with reduced length of stay. Models of co-management, different to POST, or with different performance metrics, could be tested.